Applications of Ozone for Recycling of Wastewater from Biogas Production for Electricity Generation - Tantirungruang, W.; Chancharoensook, P.; Yutthagowith, P. (My University, 2018)
This paper presents applications of ozone to recycle the wastewater from the biogas production process for electricity generation. The ozone could be generated by using electric field between polarized electrodes. In comparative experiments, three tanks were used for biogas fermentation using anaerobic microorganisms. We designed three different experimental settings as follows: 1) The one using only fresh wastewater from ethanol production process. 2) The one using recycled wastewater with ozonation. 3) The one using recycled wastewater without ozonation. The experimental results indicated that ozone could help improving the biogas production to 2.1 liters/day per 1 liter of recycled wastewater. The methane and carbon dioxide concentrations were 66. 8% and 38. 5%, respectively.
Keywords: biogas; electricity; ozonation; quality; quantity